Utilisation patterns and cost of hospital care for people living with HIV in Ireland in 2012: a single-centre study. (March 2017) - Brennan, Aline; Horgan, Mary; Jackson, Arthur; Browne, John P; Bergin, Colm J
Data on the pattern and cost of health service use by HIV patients are required for evaluations of the cost-effectiveness of new drugs and technologies as well as being essential for service planning. The aim of this study was to identify the utilisation patterns and cost of hospital care for HIV patients in a single centre in Ireland in 2012. Data on the frequency and non-drug costs of all hospital resources used by HIV patients were extracted from a hospital activity-based costing system. Cost data were analysed using a generalised linear model. A total of 328 patients, 3672 patient months, were included in this study. Patients had a mean of 4.4 scheduled infectious disease outpatient appointments per patient year; 37% of patients also used another outpatient service, 15% in-patient services, 4% day-case service and 18% emergency department services in 2012. Patients with very advanced HIV disease continue to incur a disproportionate amount of the total cost of providing care. This study provides baseline utilisation and cost data for use of both infectious-disease and non-infectious disease hospital services and will be useful for service planning in light of the likely increases in resource demands.